Green Innovation in Construction Industry and in Public Works Procurement in Hungary - Review - Boros, Anita; Kovács, László (Journal of Central European Green Innovation, 2022)
The construction industry is an important industry that determines the national economy of almost every country. Due to its productivity, the number of people it employs, and the number of enterprises involved, it is also decisive for other industries. The facilities completed as a result of public works often outlast their dreamers by decades, so it is very important that the construction industry is open to the innovative development of its operations, products and elements that provide infrastructure for others. The basic hypothesis of our study is that although a rapid regeneration took place in the construction industry after the pandemic situation, which is also supported by the number of public procurement procedures for Hungarian public works, the proportion of procedures using innovative solutions is low, as is the case with sustainability aspects. We also assumed that the share of public procurement procedures integrating R&D results and innovation partnerships is low compared to domestic public procurement.